ANDROID APPLICATION “GAMARC” TO SUPPORT THE GREEN CAMPUS BICYCLE TRANSPORTATION CONCEPT – CASE STUDY UGM YOGYAKARTA - Afrizal Abdi Musyafiq; Agung prayogo (Journal of Telematics and Informatics, 2018)
University of Gadjah Mada (UGM) is the oldest university in Indonesia located in Yogyakarta city, precisely in Bulaksumur region. In the framework of educopolis area, a conducive environment for learning process and responsive to ecology issues, the provision of campus bicycle service as one of the manifestation of the vision is required. In the process of borrowing bicycles in the preceding system exist some problems with the manual paper recording system used by some campus bicycle lending stations. As a response to the ineffectiveness of the previous campus bike lending service process, an Android – based lending application which facilitates services is necessary, concerning the mobility and touchy traits of communication among academic community that is more fluent in using the smartphone nowadays. This application is made by waterfall method using Android Studio software. Users of this application are Students, campus bike administrator, Lecturer and the internal employees of UGM (Civitas academica UGM). This research produced an UGM campus bicycle lending application called GamaRC. This application can facilitate users to make the process of borrowing and refunding the campus bike with barcode scanning facility. GamaRC application is expected to be implemented in the internal environment of UGM campus so that the concept of educopolis and green campus UGM can be fulfilled.